Garage Automation Door by Using Radio-Frequency Identification (RFID) - DUSIT, THADDEUS MADANG; NORJALI, RASIDA (Progress in Engineering Application and Technology, 2021)
The purpose of this project is to develop an independent security system that able to open the garage door automatically with the help of Radio-Frequency Identification (RFID) and Arduino Uno. This requirement has become demanded as nowadays systems are too dependent on the community. Different from an ordinary system, this project will be able to ensure the safety of the owner and to avoid the thief from entering the house through the garage. This project designed entitled “Garage Automatic Door by Using Radio-Frequency Identification (RFID)” with a simple design. This project utilized the use of an RFID system for the door opening systems. In this paper, the design and implementation of an automatic controller for the garage door. The garage door will open when the human scans the card using an RFID system and with the help of an ultrasonic sensor at a certain range. Then, the 12V DC motor is used to control the opening and closing movement of the garage door. As the result, the project is successfully conducted.